Grain dust explosions in U.S. decline again in 1983 with no fatalities - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
A further decline in grain dust explosions occurred in the U.S. in 1983 Based on explosions reported to USDA, FGIS Safety Director Ralph Regan and Robert W. Schoeff, Extension Marketing & Safety Specialist, Kansas State University. There were 13 reported explosions in 1983 compared to 14 injured. Property Damage estimates ranged from minor to $1.2 million.
Keywords: Grain dust; Dust explosions